SOCIAL MEDIA MARKETING STRATEGY TO ATTRACT NEW POTENTIAL JOB SEEKERS AND INCREASE BRAND AWARENESS IN ASIA PACIFIC REGION (A STUDY CASE OF CONNECTINGPM) - Nirmala Raihan Pitaloka Pitaloka; Ismi Darmastuti (Faculty of Economics and Business Diponegoro University, 2022)
This study employs quantitative research to establish which social media platform is appropriate for ConnectingPM in the Asia Pacific market and social media marketing strategy according to ConnectingPM’s current situations. This strategy intends to maximize company sales by increasing brand awareness and attracting new job seekers. During the internship, information was gathered through desk research and questionnaires. The research indicates that the familiarity of project management recruitment services in Asia Pacific is still low and ConnectingPM should focus more on LinkedIn to increase customer brand awareness. Social media marketing strategies are also described in this study, focusing more on LinkedIn social media, but remaining active on other social media so that social media channels can complement each other. In addition, social media content that is relevant to the ConnectingPM case is also explained.